Investment Decision Quality Improvement Model in the Context of Behavioural Finance - Kurniasari, Erika; Giovanni, Axel; Nurunnisa, Ika Amalia; Fitriani, Maulida Eka; Fajrin, Nurul Afisa; Nizhaty, Putri Zahra (Master of Management, Faculty of Economics and Business, Diponegoro University, 2024)
This study aims to identify themes, trends, and networks in the mechanisms that shape the quality of investment decisions in the context of behavioural finance using bibliometric. The results show that good financial literacy can reduce the negative influence of cognitive biases such as heuristics, framing effects, and herd mentality in investment decision-making. In addition, improved financial literacy also plays a role in moderating the effects of behavioural biases on investment decisions, resulting in more rational and profitable decisions. Therefore, financial literacy is an effective strategy to improve the quality of investment decisions by reducing the impact of cognitive biases.